FORAMINIFEROS DEL CRETACICO SUPERIOR Y TERCIARIO DEL SUBSUELO DE LA PROVINCIA SANTA CRUZ, ARGENTINA (Ameghiniana, 2013)
The paper contains the study of the S.C.3 well foraminifera, center-south of Santa Cruz province, Argentina. Fifty-six foraminiferal specia are determined, and fortyfour are described and illustrated, with a lithological description of the samples that contain them, followed by a brief review cf the micropaleontological and stratigraphical knowledges of the Cuenca Austral. The presence of Cenomanian based on the planctonic foraminifera Globigerinelloides ben- tonensis (Morrow) and Globigerina washitensis Carsey, was determined. The presence of a hiatus that probably goes from the Upper Cenomanian to the Lower Santonian is verified. It had been noted already by Leanza (1963) on surface at Ultima Esperanza region, in Chile, based on arnmonites. The microfauna of Upper Campanian-Lower Maestrichtian is described and illustrated; it is characterized by Gyroidinoides globosa (Hagenow) varo orbicella Bandy, Praebulimina kicleapoensis (Cole l, Cyclammina sp. and Allomorphina paleocenica Cushman and Piramidina minima (Brotzen ): the age assigned to this fauna is based on the presence of Heterohelix punctulata (Cushman) and the association with Eubaculites? sp. A microfauna of Eocene age that presents affinity with the one of Agua Fresca forma- tion (Todd and K.niker, 1952) is illustrated; it is characterized by. Cyclamina cancellata (Brady ), Heterolepa haidingeri (d'Orb.), Cassidulina crassa d'Orb., Trochamina? sp., Gyroi- dinoides soldanii, Quinqueloculina imperialis Hanna and Harina, corresponding ecologically to a normal salinity environment, cold waters and a deepness of no more than 200 m. It also contains the study of a Miocene microfauna in which the presence of Globigerina officinalis Subbotina, indicates -since it seems that the marine Oligocene is absent in the country (Carnacho, 1966)- that the Miocene ingression in the south of the country had begun in the Aquitanian. The samples studied belong tO a shallow water environment cha- racterized by the presence of Porosorotalia ornata (d'Orb.), from which it is results that its pre.sence in recent sediments is due to rework, and other specia that nowadays live in the present patagonian coasts.